Recovering from catastrophic disaster in Asia - Waugh, William L.; Han, Ziqiang (Emerald Publishing Limited, 2017)
Volume 18 of the Community, Environment and Disaster Risk Management series looks at how cities and countries recover from catastrophic disasters with a specific focus on Asia. Asia has experienced devastating disasters over the centuries. Proximity to the seismically active Ring of Fire and other plate boundaries, long Pacific and Indian Ocean coastlines, major river and tributary courses, desert and semi-desert areas, and other geographic features create a diversity of hazards and potential hazards. Chapters cover topics including International Humanitarian Assistance and Disaster Recovery, Disaster exceptionalism in India, Immigrant and refugee experiences in Canterbury and Tohoku, Citizen Participation in the Disaster Reconstruction Process after the Great East Japan Earthquake, and Social Capital and Changes in Post-Disaster Recovery Process in China after the 2008 Wenchuan Earthquake.
Prelims -- Disaster recovery in Asia: an introduction -- Social capital and changes in post-disaster recovery process: observations from China after the 2008 Wenchuan Earthquake -- Recovering from prolonged negative destination images in post-disaster Northern Japan -- Restoration of communities following the Great East Japan disaster: The transformation of mutual help networks through the eyes of the victims -- Lessons from disaster recovery in Japan through case studies of four earthquakes -- Citizen participation in the disaster reconstruction process: lessons from the Great East Japan earthquake -- Social vulnerability in disasters: immigrant and refugee experiences in Canterbury and Tohoku -- Disaster exceptionalism in India: The view from below -- The 2015 Nepal earthquake: from rescue to reconstruction -- International humanitarian assistance and disaster recovery in Asia -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Nature -- Natural Disasters; Natural disasters; Natural disasters -- Asia; Disaster relief -- Asia